Resiliensi Ibu Yang Memiliki Anak Down Syndrome - Rilla Sovitriana; Alissya Putri (Jayapangus Press, 2020)
Resilience is the ability of individuals in surviving to overcome the problems that exist in life and be able to develop from adversity and misery so as to be able to adapt and deal with unpleasant conditions. The purpose of this study was to determine the relationship between family support and resilience in mothers who have children with Down syndrome in Jakarta. In this study using two variables, namely family support and resilience. The population of this study was 55 respondents. Data collection uses a Likert scale and uses saturation sampling. The results shows that rx1y of 0.428 and p = 0.001 (p <0.05) Ho = rejected Ha1: there is a significant relationship and direction of a positive correlation between family social support and resilience among mothers who have children with down syndrome in Jakarta is accepted.